Fiscal fault, financial fix? Capital Markets Union and the quest for macroeconomic stabilization in the Euro Area. (April 2018) - Braun, Benjamin; Hübner, Marina
This article seeks to situate and explain the European Union's push for a Capital Markets Union – and thus for a more market-based financial system – in the broader context of macroeconomic governance in politically fractured polities. The current governance structure of the European Monetary Union severely limits the capacity of both national and supranational actors to provide a core public good: macroeconomic stabilization. While member states have institutionalized fiscal austerity and abandoned other macroeconomic levers, the European polity lacks the fiscal resources necessary to achieve stable macroeconomic conditions – smoothing the business cycle, ensuring growth and job creation and mitigating the impact of output shocks on consumption. Capital Markets Union, we argue, is the attempt of European policymakers to devise a financial fix to this structural capacity gap. Using its regulatory powers, the Commission, supported by the European Central Bank (ECB), seeks to harness private financial markets and instruments to provide the public policy good of macroeconomic stabilization. We trace how technocrats, think tanks, and financial-sector lobbyists, through the strategic use of knowledge and expertise, established securitization and market-based finance as solutions to the European Monetary Union's governance problems.